2021
DOI: 10.1002/adhm.202100259
|View full text |Cite
|
Sign up to set email alerts
|

ZnO/CPAN Modified Contact Lens with Antibacterial and Harmful Light Reduction Capabilities

Abstract: Compared with traditional glasses, the comfortable and convenient contact lens (CL) has seen an upsurge among the public. However, due to the lack of antibacterial properties of ordinary CLs, the risk of eye infection is greatly increased accordingly. On the other hand, ordinary CLs also cannot effectively reduce the short‐wavelength blue light emitted from electronic products, such as mobile phones and computers. Aiming at the above two problems, zinc oxide (ZnO)/cyclized polyacrylonitrile (CPAN) composites a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…2b), which could only be excited by some short-wavelength lights with certain cellular damage. 62 The degradation of ZPTA-G/HMA to RhB solution with different light illumination was adopted to further confirm the GL responsiveness of ZPTA-G/HMA. The results demonstrated that the GL (520 nm) group degraded fastest among all groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2b), which could only be excited by some short-wavelength lights with certain cellular damage. 62 The degradation of ZPTA-G/HMA to RhB solution with different light illumination was adopted to further confirm the GL responsiveness of ZPTA-G/HMA. The results demonstrated that the GL (520 nm) group degraded fastest among all groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Surface coating or nano-composited mixing [356,357] strategies have been widely employed as current contact lenses lack antibiotic properties. However, long-term stability and biocompatibility require further investigation.…”
Section: Novel Smart Contact Lens Materials With Extraordinary Proper...mentioning
confidence: 99%
“…The preparation of NNHs by loading the bactericidal nanoparticles in the precursor solution begins with the mixed uniform solution, which is prepared into fibers by ESP. Mainstream bactericidal nanoparticles mainly include metal (AuNPs [135,136], AgNPs [137,138]) and metal oxides (ZnO [139], CuO [140] and TiO 2 [141]), etc. The accumulation of AgNPs in mitochondria leads to mitochondrial dysfunction.…”
Section: Antibacterialmentioning
confidence: 99%